Large size mammal species of North Selangor peat swamp forest and their response to habitat quality and anthropogenic disturbances - Md Rashid, Nurfatin Adila (2017)
Malaysia’s peat swamp forest is now disappearing at alarming rate due to deforestation. Tropical peat swamp forests of Peninsular Malaysia are one of the unique ecosystems that are currently being threatened primarily for agricultural expansion. Oil palm is the most demanding commercial crop in Southeast Asia especially in developing countries such as Malaysia. To determine the mammal species richness and the response toward its richness, a camera trap survey was conducted in the North Selangor Peat Swamp Forest (NSPSF), the last remaining peat swamp ecosystem on the western coast of Peninsular Malaysia. The research was initiated in May 2013 and ended in October 2014. I measured a total of 13 attributes of local level factors and landscape level factors to investigate the relationships between these factors and mammal species recorded by camera traps. Eight local level factors were accounted for the habitat quality measurement. These were number of saplings, number of trees (DBH: less than 45cm and more than 45cm), number of palmae species, number of fallen trees (DBH: less than 45cm and more than 45cm), canopy cover and canopy height. Meanwhile, five landscape level factors were the distances to river, road, oil palm land area, forest area and compositional heterogeneity. Throughout 45 camera traps deployed randomly in the forest area, 16 species of mammal were recorded in the NSPSF. The species obtained were classified according to feeding guilds and then analyzed in response to local and landscape level factors using Generalize Linear Models (GLMs). From 2565 trap nights, a total of 5046 photos were recorded excluding the blurry and out of focus photos. Asian Tapir (Tapirus indicus) recorded in this study was listed as Endangered species under IUCN Red List. This study also documented the discovery of the Bearded Pig (Sus Barbatus) in the west coast region of Peninsular Malaysia in contrast to prior distribution studies of them. Result obtained for richness model explained the overall species richness increased significantly with areas located to the main road, palm oil plantation and areas with trees exceeding 45cm in diameter at breast height (DBH). These models also demonstrated a negative relationship with variables such as canopy height, number of sapling and distance to the river. The results also showed that the richness model according to the feeding guild has responded contrarily to local and landscape level factors. The current pressure on the NSPSF compelled the wildlife to survive on shrinking habitat that is already on the brink of extinction. The finding of the research also concludes that the existing wildlife may have adapted to the existing anthropogenic elements. However, it is crucial to monitor forest clearance and devise a mitigation plan such as forest gazettement or creating an environment-friendly area for adjacent lands. It is vital to consistently monitor the forest biodiversity through long-term researches.